2018
DOI: 10.1177/1558944717750918
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Orthopedic Hand Surgeon’s Attire on Patient Confidence and Trust

Abstract: Combining strong clinical skills with appropriate clinical attire highlighted by the physician wearing a white coat appears to be an effective way to enhance patient satisfaction while ultimately gaining the trust and respect needed to properly care for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Lands found that patients in an orthopaedic hand clinic consistently gave the highest ranking to male and female surgeons wearing a WC in seven patient-perceived qualities. 5 In our study, no comparisons existed where a greater number of respondents preferred the model without a WC to one with a WC. Therefore, for most patients who indicated a preference, a WC seems to increase association with positive traits.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Lands found that patients in an orthopaedic hand clinic consistently gave the highest ranking to male and female surgeons wearing a WC in seven patient-perceived qualities. 5 In our study, no comparisons existed where a greater number of respondents preferred the model without a WC to one with a WC. Therefore, for most patients who indicated a preference, a WC seems to increase association with positive traits.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, although comparisons within each sex allowed a preferred attire to be identified, previous studies have not published direct comparisons between men and women orthopaedic surgeons. 3 - 5 One previous study of the importance of the orthopaedic doctors' appearance from Scotland did not include any female models. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey development was based on interdisciplinary collaboration and previous similar studies that examined patient perceptions of physician attire. 7 8 9 10 11 12 13 Study data were collected using SurveyMonkey (San Mateo, California).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Yamada et al 8 reported that for 70% of patients, attire influenced their confidence in a physician. Multiple previous studies have analyzed the patient perception of physician attire 7 8 9 10 11 12 13 ; however, these were done before the COVID-19 pandemic and, as such, were focused on professionalism and trust rather than patient safety. These studies reported a preference for a formal attire accompanied by a white coat.…”
mentioning
confidence: 99%